Research on Schedule Management Method Based on Critical Chain Technology - MA Di; GUAN Xiaodi; WANG Wenjin; WEI Huanhuan; ZHU Yongfeng (Renmin Zhujiang)
Critical chain technology is a new method of project schedule management.In recent years,scholars at home and abroad have increasingly studied this technology.The research on critical chain technology mainly focuses on solving the problems of inter-project operation slack and construction delay caused by unreasonable buffer setting.In this paper,the information entropy theory is employed to build a new buffer setting model that comprehensively considers overall complexity entropy,individual complexity entropy,construction difficulty entropy,resource constraint entropy,and decision-maker preference factor.The root variance method is adopted to improve the buffer calculation formula.Then,the redundant buffer is integrated into the project buffer,and the buffer setting model is modified by absorbing possible risks.Finally,an example is discussed to verify the practicability of the model.The research shows that the proposed model can quantify the impact of risk factors on project schedule more reasonably and comprehensively,improve the accuracy of buffer setting,and effectively solve the series of problems caused by excessive import buffer.